2004
DOI: 10.1046/j.1600-0838.2003.367.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐week randomized trial comparing eccentric vs. concentric hamstring strength training in well‐trained soccer players

Abstract: NH training for 10 weeks more effectively develops maximal eccentric hamstring strength in well-trained soccer players than a comparable program based on traditional HC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
443
9
12

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(487 citation statements)
references
References 36 publications
17
443
9
12
Order By: Relevance
“…4 An etiologic risk factor commonly attributed to the high incidence of thigh strain injuries is poor eccentric muscular strength. 5,6 The temporal pattern of injury during match play also indicates that fatigue might be a factor. 2 In English professional soccer players, 47% of match-play hamstrings strains were incurred during the final 15 minutes of each half.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 An etiologic risk factor commonly attributed to the high incidence of thigh strain injuries is poor eccentric muscular strength. 5,6 The temporal pattern of injury during match play also indicates that fatigue might be a factor. 2 In English professional soccer players, 47% of match-play hamstrings strains were incurred during the final 15 minutes of each half.…”
Section: Key Pointsmentioning
confidence: 99%
“…Hagglund et al, 22 following an elite group of soccer players over a 2-year period, documented that athletes returning from hamstrings injuries were almost 3 times as likely to experience an identical injury the next season. 22 Using a prospective approach, others 1,5,23,24 have shown decreased rates of hamstrings strain after implementing multimodal intervention programs. The principal focus of the resistance exercises should be to impose an increased eccentric demand on the knee flexors and, after attaining sufficient strength, to incorporate a speed component (ie, power and endurance) into the progression.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Swimming, aquagym and cycling can be classified as aerobic or cardiovascular training. It has been suggested that athletes should better invest their time in cardiovascular training, rather than in stretching as there is some evidence that the risk of injury to muscles is more closely related to poor aerobic fitness than to lack of flexibility [29].…”
Section: Other Modalities To Prevent Hamstring Strainsmentioning
confidence: 99%
“…Mjolsnes et al 13 encontraram aumento (11%) do pico de torque dos músculos isquiotibiais após 10 semanas de treinamento excêntrico. Resultados semelhantes foram encontrados por Seger et al…”
Section: Introductionunclassified